Pelatihan Budidaya Jamur Tiram Untuk Mahasiswa Tadris Biologi Sebagai Pendukung Matakuliah Bioteknologi dan Kewirausahaan Biologi - Meyninda Destiara; Nurul Himmah; Istiqamah (Yayasan Literasi Sains Indonesia, 2022)
Oyster mushrooms (Pleurotus ostreatus) are one of the products related to conventional biotechnology where the product is a food that can be consumed. So that in the application of training in the cultivation of Oyster mushrooms is concerned about biotechnology and entrepreneurship subjects. Along with the rise of covid-19 that occurs is not a barrier to the facilitator team in performing devotion, of course with a limited scale. The devotion that is carried out is (1) Counseling, conducted online with online webinars followed by all biology students and participants from the general public. (2) Preparation, establishing a committee for advanced activities, namely training in oyster mushroom cultivation and implementation in entrepreneurship (3) Implementation of stage 1, implementation of oyster mushroom cultivation and implementation of biotechnology subjects, (4) Implementation of stage 2, implementation of biological entrepreneurship subjects by selling biologically efficacious products such as raw oyster mushrooms, (5) Monitoring and evaluation of activities: monitoring and evaluation of activities carried out by the Committee and facilitators as parties who help monitoring and evaluation which are also assisted by sources.